From hinterland granary fort to frontier mountain fortress: Initiation, construction, and expansion of the Diaoyucheng Fortress, Hechuan, China, in the wars during 1125–1279 - Wen Huang; Jiang Feng (Frontiers of Architectural Research)
The Southern Song planned and constructed the Diaoyucheng Fortress at Hezhou of the Sichuan Theatre, during the 13th century. This fortress became famous for its 36-year resistance against the Mongols and the death of Möngke Khan in 1259. Based on historical documents and data from re-analysis of archaeological report and field survey, this study explores its initiation, construction and transition, to build a coherent narrative for its transformation from a hinterland transport hub during the Song-Jin War (1125–1234) to a frontier stronghold during the Song-Mongol War (1235–1279), which experiences the establishment of Zhuanban Granary in the 1130s, the construction of Xinyuguan Fort in the 1160s–1170s, the transformation into a refuge in 1240, and the expansion into the Diaoyucheng Fortress in 1243–1279. By combining spatial analysis with military history, this study discusses how the peninsular site, the “dustpan” form, and the fort cluster were formed under the influence of military strategies in different war periods and the topography in Sichuan. With the comparisons with the fortifications across Eurasia around the same period, this study illustrates this fortress epitomizes the development of knowledge system for fortification design in ancient China, especially the river defense fortress taking advantage of topography and navy.